(untitled) (Ameghiniana, 2013)
Abstract. Mariliasuchus amarali is a notosuchian crocodylomorph found in the Bauru Basin, São Paulo State, Brazil (Adamantina Formation,Turonian–Santonian). The main trait of M. amarali is its robust construction, featuring short, laterally expanded bones. The centra of the vertebrae are amphicoelous. In the ilium, the postacetabular process is ventrally inclined and exceeds the limits of the roof of the acetabulum. M. amarali has postcranial morphological characteristics that are very similar to those of Notosuchus terrestris, though it also displays traits resembling those of eusuchian crocodyliforms (Crocodyliformes, Eusuchia). The similarity of the appendicular skeleton of M. amarali with the recent forms of Eusuchia, leads us to infer that M. amarali did not have an erect or semi-erect posture, as proposed for the notosuchian mesoeucrocodylians, but a sprawling type posture and, possibly, had amphibian habits (sharing this characteristic with the extant Eusuchia). Resumen. ESQUELETO POSCRANEANO DE MARILIASUCHUS AMARALI CARVALHO Y BERTINI, 1999 (MESOEUCROCODYLIA), DE LA CUENCA DE BAURU, CRETÁCICO SUPERIOR DE BRASIL. Mariliasuchus amarali es un crocodilomorfo notosuquio encontrado en la Cuenca Bauru, Estado de São Paulo, Brasil (Formación Adamantina, Turoniano–Santoniano). Esta especie se destaca debido al abundante número de fósiles, excavados en el Municipio de Marília, Estado de São Paulo. La mayor característica de M. amarali es su construcción robusta, mostrando huesos cortos y expandidos lateralmente. El centro de las vértebras es anficélico. En el ilium, el proceso postacetabular es ventralmente inclinado y excede los límites del techo del acetábulo. M. amarali posee características morfológicas postcraneanas que son muy similares a aquéllas de Notosuchus terrestris, aunque también muestra rasgos semejantes a los crocodiliformes eusuquios (Crocodyliformes, Eusuchia). La similitud del esqueleto apendicular de M. amarali con las formas recientes de Eusuchia, llevan a inferir que M. amarali no tenía una postura erecta o semi-erecta, como fue propuesto para los notosuquios mesoeucrocodilianos, sino una postura esparrancada y, posiblemente, poseía hábitos anfibios (compartiendo esta característica con los Eusuchia vivientes).